PROFIL USAHA TANI LAHAN KERING BERBASIS TEMBAKAU DI SUB-DAS PROGO HULU (KABUPATEN TEMANGGUNG, JAWA TENGAH) - Jaka Suyana; Naik Sinukaban; Bunasor Sanim; M Yanuar J Purwanto (Universitas Sebelas Maret, 2010)
This research was located at Progo Hulu sub watershed dry land areas, which are used for tobacco farming. The results show that the characteristics of farmers at tobacco-based farming system at Progo Hulu sub watershed generally were (a) age ranges 21-77 years old (mean 44.54 years old); (b) land ownership area ranges 0.17-2.5 ha (mean 0.66 ha); (c) total persons in a family ranges 2-8 people (mean 4-5 people); (d) the experience as farmer ranges 4-52 years (mean 22.69 years); (e) education level is low (primary school), as much of 68.8%. Based on the commodity, the highest income achieved by tobacco (IDR 16,791,522 – IDR 48,593,167 per ha), with R/C ratio 2.21-4.11; followed with red chilli (IDR 8,115,125 – IDR 33,702,750 per ha) with R/C ratio 1.31-2.37; tomato (IDR 18,081,333 per ha) with R/C ratio 1.83; onion (IDR 6,712,080 per ha) with R/C ratio 1.45; leek (IDR 6,145,000 – IDR 6,357,000 per ha) with R/C ratio 1.79; cabbage (IDR 2,608,833 – IDR 4,467,833 per ha) with R/C ratio 1.31-1.78; maize (IDR 30,333 – IDR 2,682,333 per ha) with R/C ratio 1.02-2.64; and garlic causes financially loss (-) IDR 2,200,000 – (-) IDR 2,872,000 per ha with R/C ratio 0.73-0.79.